Givers and takers in science: thriving through genuine collaboration and lasting success - Bruno de Bezerril Andrade (Journal of Evidence-Based Healthcare)
Scientific progress hinges on collaboration, trust, and the exchange of ideas. This essay explores the roles of "Givers" and "Takers" within the scientific community, emphasizing how behaviors focused on collective advancement drive innovation and enduring success. Givers foster environments of mutual respect and sustainable partnerships, while Takers, prioritizing short-term gains, risk undermining the collaborative fabric of science. Through a conceptual analysis, the manuscript highlights the importance of strategic generosity in overcoming challenges posed by Takers and underscores the necessity of institutional support for a culture of giving. The discussion concludes with a call to embrace collaborative values as a pathway to meaningful and lasting contributions in science.